Preliminary survey of the epigaeic invertebrate fauna, with particular reference to ants, in areas of different land use a Dwellingup, Western Australia - Majer, Jonathan (1977)
A pilot pitfall trap sampling programme was performed at Dwellingup, Western Australia in order to compare the epigaeic fauna in unburnt jarrah (Eucalyptus marginata), burnt jarrah, dieback-infested jarrah, pine plantations, and urban, farmed and mined areas.Analysis of similarity of the ant fauna produced a broad division into two groups. The first group consisted of a rich ant fauna of moderate equitability and was associated with only slightly modified native forest sites. The second group consisted of a less rich and, to some extent, less equitable ant fauna and was associated with sites with highly modified vegetation.The occurrence of individual species in each area is discussed in relation to forest succession and incidence of pioneer species.